Search for Higgs boson production in dilepton and missing energy final states with 5.4fb-1 of pp̄ collisions at √s=1.96TeV - Abazov, V. M. (2010)
A search for the standard model Higgs boson is presented using events with two charged leptons and large missing transverse energy selected from 5.4fb -1 of integrated luminosity in pp̄ collisions at √s=1.96TeV collected with the D0 detector at the Fermilab Tevatron collider. No significant excess of events above background predictions is found, and observed (expected) upper limits at 95% confidence level on the rate of Higgs boson production are derived that are a factor of 1.55 (1.36) above the predicted standard model cross section at mH=165GeV. © 2010 The American Physical Society.